THE FIGHT IN VELIKA HOČA IN 1905 AND ITS ECHO IN SERBIAN LITERATURE (Heritage, 2026)
Small group of seven Serbian chetniks led by Savatije Milošević and lazar Kujundžić, was killed in 1905 in Velika Hoča, on the way to Poreče. The local Albanians hosted them in their home, taking an oath not to hand them over to the Turkish authorities, but they broke the oath. The deceived Chetniks fought all night with local Albanians and Turkish soldiers, and were all killed. The paper analyzes the echo of this event in Serbian literature and the press, which served as a medium for glorifying the sacrifice and patriotism of both the Chetniks and their families. Among the victims, Lazar Kujundžić and Savatije Milošević were most mentioned, but in terms of reconstructing Chetnik (and Serbian) heroism and creating new national heroes, Kujundžić and his mother Jovanka, who was allegedly invited to identify her son and refused so as not to endanger the Serbs, were particularly inspiring. Interpretations of the event itself are predominant, but also of the events that followed, such as the identification of the dead and the fate of the Albanians who betrayed them. Under the influence of interpretations in the press, the first literary texts appeared, such as the short story by Zarija Popović, and then the celebrated Dubrovnik writer and playwright Ivo Vojnović wrote the play The Resurrection of Lazarus, which was performed on the stage of the National Theater in Belgrade. These two works, along with the verses of Milosav Jelić, built the final perception of the events in Velika Hoča in the Serbian public, tradition and culture. Literary interpretations of the battle in Velika Hoča continued in the interwar period, in the works of Grigorije Božović. After 1930, Chetnik anniversaries began to occur, and on their occasion, periodicals published appropriate articles about the Chetnik movement, memories of participants or contemporaries of their activities, biographies of dukes and Chetniks, and descriptions of Chetnik battles.
Keywords: Velika Hoča, Savatije Milošević, Lazar Kujundžić, Zarija Popović, Ivo Vojnović, Milosav Jelić, Grigorije Božović, Petar Kostić, calendar Vardar